تحليل مفهوم الحاكمية في فكر سيد قطب = An analysis of the conceptual framework of al-Ḥākimiyyah of Sayyed Quṭb - Al-Banna, Ibrahim 'Abdullah; Mohd Daud, Noor Amali (IIUM Press, International Islamic University Malaysia, 2018)
This article analyzes the conceptual framework of ‘al-hākimiyyah’ (the sovereignty) in Sayyed Quṭb’s discourse.It characterizes the definition of al-hākimiyyah, categories as well as examples of the notion in Quṭb’s point of view. The article also investigates views of scholars who support Quṭb as well as those who oppose him in regards to this notion. The study concludes that al-hākimiyyah in Quṭb’s viewpoint only acknowledges and legitimizes the sovereignty of God, and man has no right to claim the legitimacy. As part of characteristics, the understanding of al-hākimiyyah will never compromise any mixture of īmān and refusal of Divine jurisdiction together. In relation to the concept, the article also clarifies that any attempts of associating takfīr (pronouncement someone as unbeliever) to Quṭb,can be accounted as baseless accusation and unsubstantiated.